2018
DOI: 10.1039/c7ra11330g
|View full text |Cite
|
Sign up to set email alerts
|

Durable oxygen evolution reaction of one dimensional spinel CoFe2O4 nanofibers fabricated by electrospinning

Abstract: One dimensional spinel CoFe2O4 nanofibers were synthesized via the electrospinning technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…To the best of our knowledge, the SP/DP material has one of the lowest overpotentials at 10 mA cm −2 in alkaline solution among the reported perovskite oxide OER electrocatalysts (Figure c and Table S3), including DP oxides (e.g., La 2 NiMnO 6 , PrBaCo 2 O 5.75 , Sr 2 Fe 0.8 Co 0.2 Mo 0.65 Ni 0.35 O 6 , and SrCo 0.2 Fe 0.2 W 0.4 O 3−δ ) and SP oxides (e.g., F substituted Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ , SrCo 0.5 Fe 0.5 O 3−δ , SrNb 0.1 Co 0.7 Fe 0.2 O 3−δ nanorods, and LaCo 0.8 V 0.2 O 3 ). Additionally, the SP/DP material has superior catalytic activity to noble metal oxides, such as IrO 2 , hybrids, such as BC1.5MN and LSM‐20‐Co, transition metal phosphides, such as 12‐CoNiP, and spinel oxides, such as CoFe 2 O 4 and Zn 0.35 Co 0.65 O …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the SP/DP material has one of the lowest overpotentials at 10 mA cm −2 in alkaline solution among the reported perovskite oxide OER electrocatalysts (Figure c and Table S3), including DP oxides (e.g., La 2 NiMnO 6 , PrBaCo 2 O 5.75 , Sr 2 Fe 0.8 Co 0.2 Mo 0.65 Ni 0.35 O 6 , and SrCo 0.2 Fe 0.2 W 0.4 O 3−δ ) and SP oxides (e.g., F substituted Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ , SrCo 0.5 Fe 0.5 O 3−δ , SrNb 0.1 Co 0.7 Fe 0.2 O 3−δ nanorods, and LaCo 0.8 V 0.2 O 3 ). Additionally, the SP/DP material has superior catalytic activity to noble metal oxides, such as IrO 2 , hybrids, such as BC1.5MN and LSM‐20‐Co, transition metal phosphides, such as 12‐CoNiP, and spinel oxides, such as CoFe 2 O 4 and Zn 0.35 Co 0.65 O …”
Section: Resultsmentioning
confidence: 99%
“…(b) Chronopotentiometry curve of SP/DP oxide at a fixed current density of 10 mA cm −2 . (c) OER activity of various materials in 1.0 m KOH showing the overpotential at 10 mA cm −2 , including noble metal oxides (1‐IrO 2 ), double perovskite oxides (2‐La 2 NiMnO 6 , 3‐PrBaCo 2 O 5.75 , 4‐Sr 2 Fe 0.8 Co 0.2 Mo 0.65 Ni 0.35 O 6 , and 5‐SrCo 0.2 Fe 0.2 W 0.4 O 3−δ ), single perovskite oxides (6‐F substituted Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ , 7‐SrCo 0.5 Fe 0.5 O 3−δ , 8‐SrNb 0.1 Co 0.7 Fe 0.2 O 3−δ nanorods, and 9‐LaCo 0.8 V 0.2 O 3 ), hybrids (10‐BC1.5MN and 11‐LSM‐20‐Co), transition metal phosphides (12‐CoNiP), and spinel oxides(13‐CoFe 2 O 4 and 14‐Zn 0.35 Co 0.65 O).…”
Section: Resultsmentioning
confidence: 99%
“…Non-noble transition metals such as Fe, Co, Ni and Mn have attracted a lot of attention, and the compounds of transition-metals have been suggested as replaceable electrocatalysts in OER. As OER catalysts, spinel oxides, such as N-CG-CoO, 20 26) have been widely studied as advanced electrocatalysts because of their unique crystal structure and remarkable properties. Among the various spinel oxides, CoFe 2 O 4 is one of the most interesting compounds due to its high abundance, low cost, low toxicity, rich redox chemistry and high electrochemical activity.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Zhang et al reported CoFe 2 O 4 nanobers which were prepared by electrospinning technique with an overpotential of 340 mV to deliver a current density of 10 mA cm À2 in 1.0 M KOH. 26 Ding et al prepared CoFe 2 O 4 /SWNTs nanorods via hydrothermal method and compound with SWNTs by sonication, which required an overpotential of 310 mV to achieve a current density of 10 mA cm À2 in 1.0 M KOH. 28 The CoFe 2 O 4 /biomass carbon hybrid catalyst has been synthesized from sulfate reducing bacteria via enrichment of Co with porous structure and rough surfaces, and required 300 mV for generating the current density of 10 mA cm À2 in 1.0 M KOH.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the high resolution XPS spectrum of Fe 2p (Figure c) for NiFe15 sample exhibits two prominent peaks centred at around 711.5 and 724.3 eV corresponding to the binding energies of Fe 2p 3/2 and Fe 2p 1/2 , respectively, with shakeup satellite features at 720.5 eV, confirming the presence of Fe 3+ in NiFe sponge quite similar to the reference Fe 2 O 3 . Moreover, the high‐resolution O 1s spectrum of Ni and NiFe15 sponge confirms the presence of oxides on sponge surface.…”
Section: Resultsmentioning
confidence: 99%